PENERAPAN TERAPI SUPORTIF DENGAN TEKNIK GUIDANCE UNTUK MENINGKATKAN PENGHAYATAN MAKNA HIDUP PADA PENDERITA GANGGUAN BIPOLAR DI PONDOK PESANTREN AL HAMID CIBUBUR - Pardian, Delvi (Jurnal Psikologi : Media Ilmiah Psikologi, 2019)
The lowness of the total and full comprehension of meaning of life on the sufferer of the bipolar disorder is marked by feeling having no aim of life, feeling of meaningless, easy to get bored, full of desperation, lack of interest and initiative, lack of passion of work, being not care, decreasing responsibility, questioning his/her existence in this world. The aims of this research are to find out the description of the lowness of the total and full comprehension of meaning of life on the sufferer of the bipolar disorder and to apply the supportive therapy through guidance technique to raise the total and full comprehension of meaning of life on the sufferer of the bipolar disorder. The research methods that are used in this research are single case design and A-B-A design. The author uses observation, interview, and psychology tests such as WBIS, Graphic, SSCT and the intervention of supportive therapy through guidance technique. The result of intervention shows that there is a change on the subject of the research like being able to own the more meaningful life, caring more, having more responsibility, realizing her existence in this world, easy to be happy, and full of hope. Moreover, the result of the analysis of development of the intervention is supported by the result of the scale of pre-test which shows the high category and after the post-test is conducted, the result shows the middle category. The prognosis on the subject is positive in which she succeeds to improve her total and full comprehension of meaning of life.  Keywords: supportive, therapy guidance technique, bipolar disorder